Adult limbal xanthogranuloma. Issue 5 (May 1984) - Collum, L M; Mullaney, J
Abstract : An 18-year-old white man presented with a non-painful yellow raised swelling on the inferior limbus of his right eye. Systemic and ocular examination revealed no other abnormalities. The lesion was dealt with by simple excision, but when it recurred fairly soon it was removed in toto and replaced by a lamellar graft, without recurrence. Histological examination revealed a typical xanthogranuloma. The question is, why should a healthy male with no other manifestations develop a lesion like this on his limbus?